Cyanobacterial gardens: the liverwort Frullania asagrayana acts as a reservoir of lichen photobionts. Issue 3 (11th May 2016) - Cornejo, Carolina; Scheidegger, Christoph
Summary: Cyanobacteria are important mediators of unrelated lichen species, which form epiphytic communities that share the same cyanobiont. No study to date, however, has considered the role of cyanobacteria as mediator between lichens and bryophytes. In the present study, DNA barcoding (16S rDNA, rbcLX ) was used to identify filamentous cyanobacteria living in close association with members of an epiphytic liverwort‐lichen community on balsam fir in Newfoundland. This study is the first to confirm the presence of Rhizonema strains in boreal forests where they are associated with the liverwort Frullania asagrayana and several lichen species. The majority of cyanobacterial haplotypes can associate with the liverwort, however, some lichen species appear to be more selective for single or closely related haplotypes. Some Rhizonema strains were found exclusively in association with boreal lichens, while others seem to be globally distributed and involved in different lichen symbioses of unrelated fungal lineages and of varying ecological traits. Complex biological interactions in a cyanobacteria‐mediated guild are proposed here, which explains composition and dynamics in bryophyte and lichen‐dominated epiphytic communities.